THE METHODOLOGY OF USING SONGS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Narkulova , Indira Rustam qizi (Innovative Development in Educational Activities, 2023)
To date, one of the most relevant areas of recent methodological research is the search for ways to teach effective speech communication. The relevance of raising this issue becomes obvious especially in our time, when the Russian language is the key to the success of business professional cooperation. This article substantiates the expediency of using songs at the initial stage of teaching Russian as a foreign language, describes the types of tasks, as well as the mechanisms of influence of music, songs on the motivation of listeners and cadets of higher military educational institutions.